POLA PEMBINAAN EKSTRAKURIKULER SEPAK TAKRAW DI SEKOLAH MENENGAH PERTAMA NEGERI SE-KABUPATEN TEGAL 2013/2014 - Johan Bagus Panuntun; Agus Raharjo (Universitas Negeri Semarang, 2015)
The purpose of this study is to find out about the stages of development, training programs and form of support for extracurricular coaching sepak takraw in Junior High School Tegal Regency on 2013/2014. The approach used is descriptive qualitative approach, the research by providing an overview of the actual facts at this point. Data was collected through observation, interviews, and documentation. Object numbered 4 Junior High School in Tegal regency. Each school consists of four respondents, it is headmaster, coaches, and 2 participants of extracurricular sepak takraw. The results obtained are: 1) Three schools did public stage and nursery athletes, the school does not do stage coaching, 2) The coaches put together a program of exercise but training aspects are not fully developed, while the trainer does not arrange training programs, 3) Support funding of schools is good, but the support infrastructure is still lacking,. It can be concluded that 4 (four) Junior High School in Tegal regency which organizes extracurricular sepak takraw not done well coaching phase, aspects and principles of training exercises in the student-run exercise programs have not developed a comprehensive, Financial support has been good, inadequate infrastructure support and the absence of the role of relevant agencies.